(untitled) (Research, Society and Development, 2022)
Autism or Autism Spectrum is a neurophysiological part that creates difficulty and problems between brain processes, it is also characterized as a neurobiological, genetic and hereditary disorder, which means that this disorder is presented by some family member, such as the mother, father, or sibling. The study aims to highlight the benefits of hippotherapy for the treatment of the autistic spectrum. The study is of a bibliographic nature, characterized as exploratory and descriptive and with a qualitative approach. Studies were selected from the Google Scholar database. The results indicate that the benefits generated by hippotherapy are more noticeable in the motor, cognitive and social development of autistic individuals. The hippotherapy can demonstrate its degree of efficiency due to the three-dimensional movement of the horse, which stimulates movements that favor the development of those who are riding this animal. The study reiterates the need for professionals involved in this process to be specialized and for the animal used for hippotherapy to be in good hygienic conditions and to be vaccinated within days. The study concluded that hippotherapy represents an excellent treatment for the autistic spectrum, enhancing physical, biological and social aspects, stimulating greater participation in the means of coexistence.